(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of this study is to evaluate the impact of TQM on organisational performance at First Bank Plc from 2010-2019, data were sourced through secondary means from the bank and annual financial report of the bank for the years2010-2019) and staff of the bank in Ondo state based on Senatorial District in the state. Questionnaire was designed and data collected using 5-Point Likert-Scale questionnaire which was administered on sample of 196 respondents comprises of bank staff, management and customers at the bank in three Senatorial District of the state. The data was analyzed using descriptive statistic in line with graph, Regression Statistical Technique. Five hypotheses formulated were tested using Eview9 at 0.05(5%) level of significance respectively. Findings divulge that there is a significant relationship between all selected variables of employment involvement team work and trust on first bank non-financial performance at (0.090<0.05.) and also was a strong positive relationship between total quality management (TQM) through education and training of staff on market share value (MSV), total quality management (Team work) on employees’ level of job commitment and support that will bring proper total quality management at first bank and lastly, leadership structures and employee involvement on organisational sustainability had improved the standard of first bank by given more credence to the potency of sustainability of the firm at both money and capital market that has brought great performance over the years. However, the study found little research been done regarding several factors directly affected organisational performance in the area of as organisation size, culture and level of innovation. Therefore, future researches could study these impact of Total Quality Management (TQM) on organisational performance. The study recommends that Employees and Customers should be the First Bank most important asset. Thus, this will be supportive through investment in training and development and communication skill. This will enhance the strengthening of the knowledge base of their employees’ thereby enquiring those people to confront the challenges and stay ahead in the industry.